The Influence of Digital Platform Quality and Security on Decision and Satisfaction through Trust in the DANA Digital Wallet - Djaenudin, Ernie Mardiany; Prastowo, Sugeng Lubar (International Journal of Business, Law, and Education, 2024)
This research reveals several significant findings related to the factors influencing the use of the Dana digital wallet platform. The study aims to examine the impact of digital platform quality, security on decision-making, and user satisfaction through trust in the Dana digital wallet. The research was conducted among users of the Dana digital wallet application, with 166 respondents as the sample. The research method employed a quantitative approach, specifically a causal associative approach, with research instruments in the form of a Likert scale questionnaire ranging from 1 to 5. Sampling was carried out using a non-probability incidental sampling technique. The analytical approach used SEM-PLS, utilizing Smart-PLS version 4.0. The research results demonstrate that the variables of digital platform quality, security, and trust have a significant direct impact on decision-making. The user decision-making variable has the most dominant direct influence, accounting for 85.6% of user satisfaction. Furthermore, digital platform quality and security significantly influence trust directly. Additionally, digital platform quality and security also have a significant indirect impact on decision-making through trust as a mediating variable.